The use of an additional field player in handball and its implications for defensive organization and behaviours - Paulo Torres Di Gilio, João (2024)
The change in handball rules has facilitated the use of an additional field player (AFP) during matches, and the investigations on this topic are centred in offensive behaviours. The aim of this work was to identify and analyze the behaviours advocated by elite Brazilian coaches for defensive return and positioned defence during the use of the AFP. Speeches were analyzed using the Reflexive Thematic Analysis. Coaches emphasized the defensive reorganization process in two sub-themes: defensive return and instructions for AFP substitution; and positioned defence against the use of AFP. They suggest pressuring the opponents as soon as they lose the ball possession when playing with the AFP, and in the positioned defence they prefer to use defensive systems (6:0 and 5:1).